2010
DOI: 10.1089/met.2009.0036
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Adiponectin Levels in Polycystic Ovary Syndrome, Independent of Body Mass Index

Abstract: Adiponectin levels were reduced in all the women with PCOS. There seemed to be an interaction between adiponectin and PCOS pathogenesis that was independent of body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Moreover, the resulting hyperandrogenism is thought to contribute further to low synthesis of adiponectin and its receptors in adipose tissues . Our low adiponectin level in PCOS women is in agreement with others . Toulis et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the resulting hyperandrogenism is thought to contribute further to low synthesis of adiponectin and its receptors in adipose tissues . Our low adiponectin level in PCOS women is in agreement with others . Toulis et al .…”
Section: Discussionsupporting
confidence: 93%
“…The studies addressing serum adiponectin in PCOS patients are conflicting. Although some have reported decreased adiponectin levels compared to BMI‐matched controls, others have shown no difference after controlling for obesity . Whether this decline is secondary to associated obesity or IR is not clear .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding on a confirmed association of low adiponectin concentration in PCOS and its relation to insulin resistance independent of BMI [15], a good explanation for the above findings would be that hypoadiponectinemia may be due to decreased concentrations of vitamin D metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS can be considered as the most frequent cause of anovulation [13] and is a prevalent endocrine disorder among women [14]. Insulin resistance with compensatory hyperinsulinaemia and low adiponectin concentrations independent of BMI has been reported in PCOS [15]. However, calcium and vitamin D concentrations in women with PCOS and their relationship with adiponectin have not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies addressing the topic, the relationship between adiponectin and PCOS has been controversial, though a large proportion of such studies9-13) have shown that low adiponectin levels were found in the PCOS group when compared to the control group. And it is unclear so far whether adipo nectin is a primary defect or occurred secondary to or in parallel with this insulin resistance 11-14,17).…”
Section: Discussionmentioning
confidence: 99%